(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تشكل المشافي الخاصة جزءاً هاماً من القطاع الصحي بما تقدمه من خدمات متميزة, وتشكل رديفاً هاماً لمشافي القطاع العام في استيعاب الحالات المرضية بكافة أنواعها, من هنا فإن وجود إدارة خاصة بالترويج في هذه المشافي يشكل ضرورة هامة وملحة كونه يساعد إدارة المشفى في الحصول على المعلومات اللازمة للتحسين والتنبؤ بالمشكلات المستقبلية واغتنام الفرص, وبالتالي خلق التأثير الإيجابي في سلوك الأفراد. يهدف هذا البحث إلى معرفة مدى التزام المستشفيات الخاصة في محافظة اللاذقية بعناصر مزيج ترويجي يساعدها على التعريف بخدماتها الصحية, وانتهى البحث إلى النتائج التالية: ضعف اعتماد المستشفيات الخاصة على عناصر المزيج الترويجي من إعلان وبيع شخصي, وعلاقات عامة, وتنشيط مبيعات في الترويج لخدماتها الصحية - عدم وجود إستراتيجية تسويقية وترويجية واضحة لدى المستشفيات عينة الدراسة - إضافة إلى غياب إدارة خاصة بالتسويق في المستشفيات موضوع الدراسة تقوم باتخاذ القرار حول صورة المستشفى التي تريد الإدارة ترسيخها في أذهان الآخرين. Private hospitals play an important role in the health services sector for their excellent services, and they work along with public hospitals in treating all causes of disease and patients. So, there is an insistent need to create special department for promotion because it provides the hospital administration with the necessary information for developing and forecasting the future problems and seizing the opportunity and help it influence positively on the individual behavior. This research aims to recognize the level of lattakia private hospitals adherence to promotion mixture elements which help them to promote their services. The research ends up to the following results: the private hospitals don’t depend on the elements of promotion mixture, from personal selling and advertising, public relationships, to sales promotion in promoting their health services. And there is no specific marketing and promotion strategy in hospitals under study, In addition, the absence of special department of marketing in hospitals under study that makes decision about the image that the hospital administration want to create in minds of peoples.